2014
DOI: 10.1155/2014/850926
|View full text |Cite
|
Sign up to set email alerts
|

Random Forest Based Coarse Locating and KPCA Feature Extraction for Indoor Positioning System

Abstract: With the fast developing of mobile terminals, positioning techniques based on fingerprinting method draw attention from many researchers even world famous companies. To conquer some shortcomings of the existing fingerprinting systems and further improve the system performance, on the one hand, in the paper, we propose a coarse positioning method based on random forest, which is able to customize several subregions, and classify test point to the region with an outstanding accuracy compared with some typical cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 18 publications
(21 reference statements)
0
15
0
Order By: Relevance
“…When applied to LF techniques, random forests outperform other machine learning methods such as artificial neural nets and support vector machines while requiring less training time complexity (Mo et al . ). Random forest models can also provide the user with the distribution of conditional predictions produced by the trees, rather than only a single conditional mean for the forest.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…When applied to LF techniques, random forests outperform other machine learning methods such as artificial neural nets and support vector machines while requiring less training time complexity (Mo et al . ). Random forest models can also provide the user with the distribution of conditional predictions produced by the trees, rather than only a single conditional mean for the forest.…”
Section: Methodsmentioning
confidence: 97%
“…Random forests are an ensemble machine learning method that combine multiple models based on 'weak' subsets of the learning data to create a single model with high accuracy (Breiman 2001). When applied to LF techniques, random forests outperform other machine learning methods such as artificial neural nets and support vector machines while requiring less training time complexity (Mo et al 2014). Random forest models can also provide the user with the distribution of conditional predictions produced by the trees, rather than only a single conditional mean for the forest.…”
Section: E S T I M a T I N G T A G L O C A T I O Nmentioning
confidence: 99%
“…Jedari et al [12] compared the RF with KNN and a rules-based classifier (JRip), and the results indicated that the RF classifier presents the best performance as compared to KNN and JRip classifiers with positioning accuracy higher than 91%. Mo et al [13] proposed a coarse positioning method based on RF, which is able to customize several subregions, and test point to the region with an outstanding accuracy compared with some typical clustering algorithms.…”
Section: Related Workmentioning
confidence: 99%
“…Mo et al [21] proposed the usage of kernel PCA (KPCA) algorithm for the coarse-level prediction of manually labelled cluster using Random Forest. ey derived trained matrices from extracted KPCA features and prepared subradio maps.…”
Section: Mobile Information Systemsmentioning
confidence: 99%